2021
DOI: 10.1111/ene.14787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on stroke teleconsultations in Germany in the first half of 2020

Abstract: Background and purpose The effects of the coronavirus disease 2019 (COVID‐19) pandemic on telemedical care have not been described on a national level. Thus, we investigated the medical stroke treatment situation before, during, and after the first lockdown in Germany. Methods In this nationwide, multicenter study, data from 14 telemedical networks including 31 network centers and 155 spoke hospitals covering large parts of Germany were analyzed regarding patients' char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The absence of a relationship between socioeconomic status and goal achievement may reflect our crude method of quantifying socioeconomic status, the relative affluence of the surrounding areas or a true lack of an effect. Our overall findings on patient and clinician satisfaction are broadly in line with other studies and adds to the body of evidence produced both prior to and as a result of the pandemic [13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The absence of a relationship between socioeconomic status and goal achievement may reflect our crude method of quantifying socioeconomic status, the relative affluence of the surrounding areas or a true lack of an effect. Our overall findings on patient and clinician satisfaction are broadly in line with other studies and adds to the body of evidence produced both prior to and as a result of the pandemic [13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 87%
“…Four hundred and thirty clinician questionnaires were received from 18 clinicians (2 Clinical Nurse Specialists, 16 Consultant Neurologists), all describing consultations with different patients. Within these, 290 consultations (67%) had a corresponding patient questionnaire (80 postal questionnaires, 210 by telephone); the demographics of responders were not significantly different to non-responders (Table S1, Supplementary Data).…”
Section: Questionnaire Demographicsmentioning
confidence: 99%
“…We are aware of several studies both nationally [31][32][33] as well as internationally [34][35][36][37] reporting declines in stroke incidence and/or telestroke consultations during government-mandated lockdowns.…”
Section: Sars-cov-2 Pandemicmentioning
confidence: 99%
“…This decrease was mainly related to patients with clinical presentation of transient ischemic attack and minor stroke, whereas admissions of patients with severe stroke did not decrease [2,3]. Furthermore, a significant reduction of telemedical and telemedical stroke consultations has been reproted during the initial lockdown pandemic period [4]. It has been pointed out that patients themselves, as well as the physicians who treated them, were often hesitant to go to the hospital due to the fear of infection.…”
Section: Acute Stroke Care During the Covid-19 Pandemicmentioning
confidence: 99%
“…The question of the impact on administration of intravenous thrombolysis (IVT) has also been an issue. A German national study investigating the effects of the COVID‐19 pandemic on telemedical care reported a nonsignificant trend toward a lower proportion of IVT recommendations ( p = 0.052) [4]. Furthermore, a significant decrease for administered IVT has been reported in Italy (26%) [3], China (26.7%, p < 0.0001) [5], and France (43% vs. 51%, p = 0.029) [7] compared to nonpandemic periods.…”
mentioning
confidence: 99%